The Year's Work in the Oddball Archive - Eburne, Jonathan P. (Jonathan Paul); Roof, Judith, 1951- (Book collections on Project MUSE., 2016)
The modern age is no stranger to the cabinet of curiosities, the freak show, or a drawer full of odds and ends. These collections of oddities engagingly work against the rationality and order of the conventional archive found in a university, a corporation, or a governmental holding. In form, methodology, and content, The Year's Work in the Oddball Archive offers a counterargument to a more reasoned form of storing and recording the avant-garde (or the post-avant-garde), the perverse, the off, the bent, the absurd, the quirky, the weird, and the queer. To do so, it positions itself within the history of mirabilia launched by curiosity cabinets starting in the mid-fifteenth century and continuing to the present day. These archives (or are they counter-archives?) are located in unexpected places-the doorways of Katrina homes, the cavity of a cow, the remnants of extinct animals, an Internet site-and they offer up "alternate modes of knowing" to the traditional archive.